2015
DOI: 10.1017/s0261444814000263
|View full text |Cite
|
Sign up to set email alerts
|

Instructed pragmatics at a glance: Where instructional studies were, are, and should be going

Abstract: This paper brings together the research and developments of instructed pragmatics over the past three decades by reporting the synthesis findings of instructional intervention studies in interlanguage pragmatics. Two questions have guided this investigation: (1) is instruction effective in learning pragmatics?; and (2) what methods are most effective in learning pragmatics? Exhaustive electronic bibliographical searches yielded a body of 58 instructional intervention studies for the review. Findings across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
206
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(233 citation statements)
references
References 90 publications
18
206
0
9
Order By: Relevance
“…From the above results we can claim that implementing pedagogical intervention in the EFL classroom had a positive effect on both the amount and type of apology formulas used by learners immediately after being engaged in the instructional treatment. These findings therefore confirm previous ILP research supporting the fact that instruction does make a difference in the pragmatic realm (see Jeon and Kaya 2006;Takahashi 2010;Taguchi 2011Taguchi , 2015 for a review), and are in line with previous studies that have particularly examined the teachability of the speech act of apologies in FL settings (Eslami-Rasekh et al, 2004;Eslami-Rasekh and Eslami-Rasekh, 2008;Eslami-Rasekh and Mardani, 2010;Birjandi and Derakhshan, 2013;Simin et al, 2014;Derakhshan and Eslami-Rasekh, 2015).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…From the above results we can claim that implementing pedagogical intervention in the EFL classroom had a positive effect on both the amount and type of apology formulas used by learners immediately after being engaged in the instructional treatment. These findings therefore confirm previous ILP research supporting the fact that instruction does make a difference in the pragmatic realm (see Jeon and Kaya 2006;Takahashi 2010;Taguchi 2011Taguchi , 2015 for a review), and are in line with previous studies that have particularly examined the teachability of the speech act of apologies in FL settings (Eslami-Rasekh et al, 2004;Eslami-Rasekh and Eslami-Rasekh, 2008;Eslami-Rasekh and Mardani, 2010;Birjandi and Derakhshan, 2013;Simin et al, 2014;Derakhshan and Eslami-Rasekh, 2015).…”
Section: Resultssupporting
confidence: 89%
“…The effect of instructional intervention in the development of learners' pragmatic competence in both second language (L2) and foreign language (FL) contexts has aroused the interest of an increasing number of interlanguage pragmatics (ILP) researchers over the last decades (see Jeon and Kaya, 2006;Takahashi, 2010;Taguchi 2011Taguchi , 2015 for a review of the research undertaken). Results from this investigation have demonstrated the positive role of engaging learners in an instructional period and the teachability of all pragmatic aspects being examined (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One of the interesting findings in the review of pragmatics instruction cited above (Taguchi, 2015) was that implicit teaching of pragmatics was found to be as effective as explicit teaching if it involved noticing and processing activities. In other words, having learners first derive the target form-function-context mappings from input and then reinforce the mappings by processing them consciously had an impact, and it was also found that engaging learners in this process clearly called for an informed teacher.…”
Section: The Challenges Of Learning Pragmaticsmentioning
confidence: 99%
“…Taguchi (2015), for example, reviewed 58 studies over the last 30 years focusing on the teaching of pragmatics in TL instruction. One finding from this exhaustive study was that the explicit teaching of pragmatics can make a difference for TL learners.…”
Section: Introductionmentioning
confidence: 99%
“…The role of pragmatic instruction in formal academic settings has been one of the main investigated areas within the field of interlanguage pragmatics in the last decades (see Takahashi, 2010;Taguchi, 2015 for a review of the research conducted). Results from this research have overall shown the benefits of engaging learners in an instructional period as well as the teachability of all pragmatic aspects being examined (i.e.…”
Section: Introductionmentioning
confidence: 99%